Endogenously Generated Omega‐3 Fatty Acids Attenuate Vascular Inflammation and Neointimal Hyperplasia by Interaction With Free Fatty Acid Receptor 4 in Mice - Li, Xinzhi (J Am Heart Assoc, 2015)
BACKGROUND: Omega‐3 polyunsaturated fatty acids (ω3 PUFAs) suppress inflammation through activation of free fatty acid receptor 4 (FFAR4), but this pathway has not been explored in the context of cardiovascular disease. We aimed to elucidate the involvement of FFAR4 activation by ω3 PUFAs in the process of vascular inflammation and neointimal hyperplasia in mice. METHODS AND RESULTS: We used mice with disruption of FFAR4 (Ffar4(−/−)), along with a strain that synthesizes high levels of ω3 PUFAs (fat‐1) and a group of crossed mice (Ffar4(−/−)/fat‐1), to elucidate the role of FFAR4 in vascular dysfunction using acute and chronic thrombosis/vascular remodeling models. The presence of FFAR4 in vascular‐associated cells including perivascular adipocytes and macrophages, but not platelets, was demonstrated. ω3 PUFAs endogenously generated in fat‐1 mice (n=9), but not in compound Ffar4(−/−)/fat‐1 mice (n=9), attenuated femoral arterial thrombosis induced by FeCl(3). Neointimal hyperplasia and vascular inflammation in the common carotid artery were significantly curtailed 4 weeks after FeCl(3) injury in fat‐1 mice (n=6). This included greater luminal diameter and enhanced blood flow, reduced intima:media ratio, and diminished macrophage infiltration in the vasculature and perivascular adipose tissue compared with control mice. These effects were attenuated in the Ffar4(−/−)/fat‐1 mice. CONCLUSIONS: These results indicate that ω3 PUFAs mitigate vascular inflammation, arterial thrombus formation, and neointimal hyperplasia by interaction with FFAR4 in mice. Moreover, the ω3 PUFA–FFAR4 pathway decreases inflammatory responses with dampened macrophage transmigration and infiltration.